Women’s Roles In A Rural Indigenous Community - Jane, Buncuan; Juna, Liau; Zabidah, Putit (2018)
Introduction: Women are said to be the agent for development. They have significant roles in the quality of her family as well as their community. Aims: This study is aimed at uncovering the roles of women of a rural indigenous community. Method: Focus group and in-depth interview with participants were employed to explore the roles of women in three rural Bisaya villages in Limbang, Sarawak. Data were analysed thematically. Results: This study highlights that in the rural community, women are mothers, wives, child-minders, domestic helpers, manager of home affairs as well as the carer of the family. They are the ones who ensure that children grow up as healthy productive individuals. Women are also involved in the family economy where they participated in income generating activities either in the farm or selling jungle produce. It is also noted that mothers also used traditional medicine for their family and self-prescribed medications when they or their family members are not well. Conclusion: This study highlights the important roles of women in the rural settings. The findings could enable health professionals and significant others to better understand the behaviour and attitudes of mothers as well as to assist the rural women to empower themselves. This study is also useful in planning and justifying future interventions of communities in the rural settings.